Realization of a spin-1/2 Kondo necklace model with magnetic field-induced coupling switch - Hironori Yamaguchi; Yu Tominaga; Takanori Kida; Koji Araki; Takashi Kawakami; Yoshiki Iwasaki; Kenta Kimura; Masayuki Hagiwara (Physical Review Research)
The theoretical Kondo necklace model, which simplifies the Kondo lattice model by focusing on spin degrees of freedom, provides a valuable framework for understanding spin-related quantum phenomena. However, it has not been applied to real materials until now. We present a realization of a spin-1/2 anisotropic Kondo necklace model using a complex of radical and Co spins. Electron spin resonance reveals anisotropic g values and an Ising-type exchange interaction with Co spin. The specific heat measurements demonstrate Schottky-type behavior, suggesting a Kondo singlet state with an energy gap in the excitation spectrum. Our findings suggest that a magnetic field can decouple Kondo interactions, unveiling a different mechanism for controlling Kondo coupling. This offers other opportunities for quantum technologies, particularly in the development of tunable qubits for quantum computing and spintronic devices, where precise control over spin interactions is essential.